PENGARUH INTERNET FINANCIAL REPORTING (IFR), TINGKAT PENGUNGKAPAN DAN KETEPATAN WAKTU (TIMELINES) PENYAMPAIAN INFORMASI KEUANGAN WEBSITE TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Yang Listing di JII Periode 2008-2012) - Setyarini, Dini; Praptitorini Soewito, Mirna Dyah (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
This study aims to analyze the influence of Internet Financial Reporting (IFR) , Level Disclosure and Timeliness ( Timelines ) Submission of Financial Information Website On The Stock Market . Sample in this study consisted of 70 companies listed in the Jakarta Islamic Index ( JII ) from 2008-2012. Data analysis uses multiple regression analysis.The results of hypothesis testing showed that the IFR has a significant influence on the abnormal stock returns, the level of disclosure has negative effect on abnormal stock returns and timeliness has no significant effect on abnormal stock returns.